HERPETOFAUNA DIVERSITY OF UJUNG KULON NATIONAL PARK AN INVENTORY RESULT IN 1990 - Hellen Kurniati; William Crampton; Anna Goodwin; Andrew Lockett; Steven Sinkins (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2001)
A seven week study of the Ujung Kulon National Park, West Java, Indonesia was conducted between July 29 and 17 September 1990. The purpose of the study was to compile an inventory of the reptile and amphibian species present in the National Park. 14 Anura, 16 Lacertilia, 17 Ophidian, 2 Testudinta and one Crocodile species were identified. Two Lacertilia, one Testudinata and 10 Ophidiasprecies are new record for the park. A tentative comparison was made between our result and a study of the region by Martens (1957) in 1955 and 1956. Management suggestion for the conservation of herpetofauna of Ujung Kulon National Park are discussed along with suggestion for further research.